Nutrient Composition, Antioxidant Andantiproliferative Properties of Chilli and Tomatocultivated by Fertigation and Conventional Methods - Abd. Mokti @ Mukti, Nor Ashikeen (2005)
Chilli (Capsicum annuum) and tomato (Lycopersicon esculentum) are two fruittype vegetables which are commonly found in multiethnic Malaysians' daily menu. They are widely consumed, easily available and edible in a variety of ways. Chillies and tomatoes which are found in the local markets are usually grown by farmers using the conventional way of cultivation, i.e. soil-based method. Fertigation is a relatively new cultivation technique in Malaysia which uses nutrient solution for the growth of the plants instead of relying on the soil as the nutrient provider. For this research, both chilli and tomato plants were cultivated in MARDI and the green and red fruits of both plants were later analysed in UPM. Proximate analyses were carried out to determine the content of macro and micronutrients of the individual plants. Their antioxidant activities determined by Beta-carotene bleaching and DPPH Assay, and antiproliferative properties (MTT Assay) were also determined. All the data of the individual plant was later compared between the two cultivation methods as well as between green and red fruits of the plants. Overview of results showed significant differences in the content of certain macronutrients. Significant differences were exhibited in the contents of antioxidant vitamins (A, C and E) of both plants. Generally, the contents of minerals in the samples were not significantly different when compared between cultivation techniques. On the contrary, the differences were significant between green and red fruits of the plants. Lycopene, as well as total phenolics contents were significantly different between conventional and fertigation red tomato. Chilli and tomato in both cultivation methods showed antioxidant activities but they were not significant in low concentrations. The crude ethanolic extracts of both plants did not display potent antiproliferative properties, since ICso values were only obtained from one cancer cell lines, i.e. cervical cancer (HeLa) out of five tested at 5- 100 pg/ ml concentration range. Therefore, it can be generalized that green and red chilli, as well as green tomato cultivated using fertigation technique produce nutritionally higher quality of yields, whereas conventional red tomato is of higher quality compared with its fertigation counterpart. Conclusively, fertigation produces nutritionally superior yields than that of conventional.